Diffusion in a one-dimensional zeolite channel: an analytical and numerical study - Chatterjee, Sakuntala; Schütz, Gunter M. (Diffusion Fundamentals, 2009)
Czaplewski et al. have demonstrated in an experiment that in the presence of strongly adsorbed hydrocarbon molecules inside a narrow, effectively one-dimensional zeolite channel, the effective desorption temperature of the weakly adsorbed hydrocarbon component is substantially increased. To explain their experimental data qualitatively, we propose a simple lattice gas model involving the diffusion of hardcore particles on a one-dimensional lattice. We present exact calculation and dynamical Monte Carlo simulations to show that taking into account an Arrhenius dependence of the single molecule diffusion coefficient on temperature, one can explain many significant features of the temperature programmed desorption profile observed in experiments.